2019
DOI: 10.1111/ijfs.14117
|View full text |Cite
|
Sign up to set email alerts
|

The soluble fraction of soy protein peptic hydrolysate reduces cholesterol micellar solubility and uptake

Abstract: Summary Previous studies have demonstrated that the undigested or insoluble high molecular fraction of soy protein exerts a lowering effect on serum cholesterol by inhibiting the absorption of cholesterol in the intestinal tract. The aim of this study was to investigate the interaction between the soluble fraction of soy protein peptic hydrolysate and dietary mixed micelles (DMMs) for cholesterol micellar solubility and uptake. The collected soluble tofu peptic hydrolysate (STPH) components, generated from har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Soy protein isolate (SPI) contains at lowest 90% protein (dry basis) and is a good substitute for meat protein because of its low-cost, less allergenic, and well-balanced essential amino acid composition (Day, 2013). SPI was reported to possess a myriad of health benefits, such as anticarcinogenic, antiinflammatory, and antioxidative, reducing cholesterol level (Jia, Tian, Zhang, Fan, & Zhao, 2019) and the risk of hyperlipidemia (Nishinari, Fang, Guo, & Phillips, 2014), inhibiting the promotion of liver tumors in mice fed a high-fat liquid diet (Eller & Reimer, 2010), which could offer novel applications in chemoprevention or adjunctive treatments (Chen & Hsieh, 2019). Because of its biodegradability, unique structural properties, and good processing performance, SPI is widely used as the biodegradable composite films (Jiang, Tang, Wen, Li, & Yang, 2007;Wang et al, 2014) and the carrier material in encapsulation of bioactive flavonoids in recent years (Wang & Wang, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Soy protein isolate (SPI) contains at lowest 90% protein (dry basis) and is a good substitute for meat protein because of its low-cost, less allergenic, and well-balanced essential amino acid composition (Day, 2013). SPI was reported to possess a myriad of health benefits, such as anticarcinogenic, antiinflammatory, and antioxidative, reducing cholesterol level (Jia, Tian, Zhang, Fan, & Zhao, 2019) and the risk of hyperlipidemia (Nishinari, Fang, Guo, & Phillips, 2014), inhibiting the promotion of liver tumors in mice fed a high-fat liquid diet (Eller & Reimer, 2010), which could offer novel applications in chemoprevention or adjunctive treatments (Chen & Hsieh, 2019). Because of its biodegradability, unique structural properties, and good processing performance, SPI is widely used as the biodegradable composite films (Jiang, Tang, Wen, Li, & Yang, 2007;Wang et al, 2014) and the carrier material in encapsulation of bioactive flavonoids in recent years (Wang & Wang, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…At a comparable concentration, the MCI of the complexation digest is higher than that of the reported synthetic peptide (31.6%) and preheated SPI (36.2%) (Fig. 6(B)), 27,36 and they had been proved to act as an inhibitor of cholesterol absorption in vivo 37,38 . The observations indicated that a simple complex with SPI greatly improved in vitro cholesterol‐lowering activity of PS.…”
Section: Resultsmentioning
confidence: 76%
“…Three soybean globulin glycin peptides (IAVPTGVA, IAVPGEVA, and LPYP) downregulated the catalytic activity of HMGCoAR, activated the LDLR-SREBP2 pathway, and improved the ability to absorb LDL in vitro, which in turn regulated the cholesterol metabolism of HepG2 cells [78]. In another study, digested soybean protein hydrolysates reduced the solubility of dietary cholesterol micelles by 37.6% and the absorbability by 18.99%, respectively, in Caco-2 cells [79].…”
Section: The Effect Of Soybean Peptides On Cvdmentioning
confidence: 97%